2012
DOI: 10.1039/c2jm15041g
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of a interleaved expanded graphite-embedded sulphur nanocomposite as cathode of Li–S batteries with excellent lithium storage performance

Abstract: This paper reports the facile synthesis of a unique interleaved expanded graphite-embedded sulphur nanocomposite (S-EG) by melt-diffusion strategy. The SEM images of the S-EG materials indicate the nanocomposites consist of nanosheets with a layer-by-layer structure. Electrochemical tests reveal that the nanocomposite with a sulphur content of 60% (0.6S-EG) can deliver the highest discharge capacity of 1210.4 mAh g À1 at a charge-discharge rate of 280 mA g À1 in the first cycle, the discharge capacity of the 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(105 citation statements)
references
References 48 publications
(43 reference statements)
3
102
0
Order By: Relevance
“…the initial capacity first increases from 856 mA·h/g for T_BC-S-40% to 961 mA·h/g for T_BC-S-50%, and then dramatically decreases to 618 mA·h/g for T_BC-S-60% at 800 mA/g rate. After 150 cycles, the T_BC-S-50% also exhibits the highest reversible capacity of 550 mA·h/g, implying the high utilization of the active sulfur in the composite with around 50 wt.% sulfur loading [30,37]. This clearly shows that the sulfur embedded into the bamboo carbon can directly impact the overall performance of the nanocomposite.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…the initial capacity first increases from 856 mA·h/g for T_BC-S-40% to 961 mA·h/g for T_BC-S-50%, and then dramatically decreases to 618 mA·h/g for T_BC-S-60% at 800 mA/g rate. After 150 cycles, the T_BC-S-50% also exhibits the highest reversible capacity of 550 mA·h/g, implying the high utilization of the active sulfur in the composite with around 50 wt.% sulfur loading [30,37]. This clearly shows that the sulfur embedded into the bamboo carbon can directly impact the overall performance of the nanocomposite.…”
Section: Resultsmentioning
confidence: 71%
“…This clearly shows that the sulfur embedded into the bamboo carbon can directly impact the overall performance of the nanocomposite. On the one hand, if the sulfur content is too low (e.g., 40%), the polysulphides formed in the charge process can readily dissolve in the organic electrolyte solution, leading to a severe shuttle phenomenon which will cause lower sulfur utilization [37]. On the other hand, if the sulfur content is too high (e.g., 60%), insoluble Li 2 S 2 or Li 2 S having lower conductivity can readily be produced during the discharge process, resulting in the lower sulfur utilization percentage and rapid decline of the specific capacity [37].…”
Section: Resultsmentioning
confidence: 99%
“…The SGC with 63.6% sulfur content yielded the highest stable capacity, signifying the maximal utilization of sulfur in the SGC electrode. In our previous studies of sulfur-carbon composites including sulfur/ordered mesoporous carbon and sulfur/expanded graphite [26,30], we found by systematic variation of the sulfur content that the optimum sulfur loading for generating the best cycling performance in composites is ca. 60%.…”
Section: Resultsmentioning
confidence: 98%
“…Various carbonaceous materials such as mesoporous carbon [25,26], carbon nanotubes [27][28][29], and carbon spheres [16] have been used as sulfur cathode support materials to improve the electrochemical performance of Li-S batteries. Sun's group has investigated a variety of carbon-sulfur composite cathode materials including sulfur/ordered mesoporous carbon [26] and sulfur/expanded graphite [30]. They demonstrated that such carbon-sulfur composites with unique structures could significantly improve the cycleability and rate capability of the sulfur cathode.…”
Section: Introductionmentioning
confidence: 98%
“…In order to operate the lithium-sulfur battery, conductive agents should be introduced into the sulfur (by synthesizing composites of sulfur/conductive agents). It has been reported that mesoporous carbon, multiwalled carbon nanotubes, carbon fibre, reduced graphene oxide, and carbon black have all been applied to improve the electrochemical performance of the sulfur cathode in lithium/sulfur batteries [5,6,[8][9][10][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%